2021
DOI: 10.1128/aac.00152-21
|View full text |Cite
|
Sign up to set email alerts
|

SpoT-Mediated NapA Upregulation Promotes Oxidative Stress-Induced Helicobacter pylori Biofilm Formation and Confers Multidrug Resistance

Abstract: Recently, there is increased incidence of drug-resistant Helicobacter pylori infection. Biofilm formation confers multidrug resistance to bacteria. Moreover, it has been found that the formation of biofilm on the surface of gastric mucosa is an important reason for the difficulty of eradication of H. pylori. The mechanisms underlying H. pylori biofilm formation in vivo have not been elucidated. Reactive oxygen species (ROS) released by the host immune cells in response to H. pylori infection cannot effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 73 publications
2
23
0
Order By: Relevance
“…The expression of adhesins increases during the transition from the planktonic to the biofilm phase ( Krzyżek et al, 2020 ). Several studies have shown that adhesive proteins, such as NapA , AlpB , SabA , BabA , Homb , LabA and HopZ are involved in biofilm formation ( Cooksley et al, 2003 ; Yang et al, 2011 ; Acio-Pizzarello et al, 2017 ; Servetas et al, 2018 ; Zhao et al, 2021 ). Compared to wild-type strains, ArsRS mutants had high surface attachment and biofilm production, and the expression of genes encoding outer membrane proteins was increased in these mutants, including AlpB , SabA , BabA , Homb , LabA and HopZ ( Acio-Pizzarello et al, 2017 ; Servetas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of adhesins increases during the transition from the planktonic to the biofilm phase ( Krzyżek et al, 2020 ). Several studies have shown that adhesive proteins, such as NapA , AlpB , SabA , BabA , Homb , LabA and HopZ are involved in biofilm formation ( Cooksley et al, 2003 ; Yang et al, 2011 ; Acio-Pizzarello et al, 2017 ; Servetas et al, 2018 ; Zhao et al, 2021 ). Compared to wild-type strains, ArsRS mutants had high surface attachment and biofilm production, and the expression of genes encoding outer membrane proteins was increased in these mutants, including AlpB , SabA , BabA , Homb , LabA and HopZ ( Acio-Pizzarello et al, 2017 ; Servetas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…NapA is a surface protein that attracts and activates neutrophils and promotes endothelial adhesion and production of oxygen radicals and chemokines ( D’Elios et al, 2007 ). When Helicobacter pylori is exposed to oxidative stress, NapA is highly expressed to resist oxygen stress injury, thus relieving bacterial survival pressure and promoting the formation and aggregation of EPS to promote biofilm formation ( Cooksley et al, 2003 ; Zhao et al, 2021 ). Another study also showed that NapA plays a role in adhesion to a substratum and H. pylori and hence influences biofilm formation ( Yang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“… 27 SpoT has been implicated in biofilm formation in multi-drug resistant bacteria by upregulating the efflux pump HP1174 and the neutrophil-activating protein (NapA; HP0243). 28 , 29 The transporter proteins HP0939, HP0497, and HP0471 are implicated in H. pylori biofilm formation. 30 …”
Section: Helicobacter Pylori Biofilmmentioning
confidence: 99%
“…Biofilms can enhance resistance to antibiotics, improve the persistence and survival rate in the host, and reduce the success rate of treatment [ 5 ]. At present, the regulatory process of H. pylori biofilm formation has not been fully explained, and in particular, transcriptome research on H. pylori biofilms remains limited [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%